Building and Sustaining National Educational Technology Agencies : Lessons, Models and Case Studies from Around the World - Trucano, Michael; Dykes, Gavin (World Bank, Washington, DC, 2017)
National educational technology agencies (‘ICT/education agencies’, and their functional equivalents) play important roles in the implementation and oversight of large scale initiatives related to the use of information and communication technologies in education in many countries. That said, little is known at a global level about the way these organizations operate, how they are structured, and how they typically evolve over time. By documenting emerging lessons from the histories of various national educational technology agencies and their functional equivalents, which are typically responsible for similar roles but which can differ radically in form by country and over time, it is hoped that this publication can help inform perspectives of decision makers considering how to create and support such an institution, the forms it might take, what roles it might take on, and how these forms and roles might be expected to evolve over time. Case studies from Korea (KERIS), Malaysia (Smart Schools), England (Becta), Chile (Enlaces), Armenia (NaCET), Uruguay (Plan Ceibal); Indonesia (PUSTEKKOM), Costa Rica (Omar Dengo Foundation), Thailand (Schoolnet Thailand), Australia (EdNA) and the Philippines are included, as well as a discussion of general lessons from international experiences, and pointers to other notable institutions around the world.